Heavy metal changes related to land use changes in a karst area: a case study in Changshun, Guizhou Province, China - Jiang, Xin; Wang, Xingfu; Liu, Yi; Huang, Yu; Huang, Xianfei (Frontiers in Environmental Science, 2024)
Karst areas are often characterized by fragile ecological systems, and environmental pollution has increased the pressures on people living in such regions. This study aimed to investigate the status of pollution caused by heavy metals (Pb, Cd, Hg, As, and Cu) in soils based on different land uses in Changshun County, a karst area in southwestern China. Soil samples were collected from natural forestlands (NFLs), natural brush lands (NBLs), natural pasture lands (NPLs), artificial forestlands (AFLs), artificial brush lands (ABLs), and artificial pasture lands (APLs) for evaluation. The results suggest that the soil profile characteristics of the heavy metals studied herein vary significantly among different land uses. The heavy metal concentrations in all soil samples collected from NFLs were lower than those in samples from other land uses. Forest trees can protect soil from heavy metal pollution caused by atmospheric deposition; this is especially true for Hg. In cultivated forestlands and brush lands, special attention should be devoted to Cd pollution in the soil, which may be caused by the use of fertilizers. Changing both natural and artificial pastoral lands to forestlands could benefit the local ecosystems as it may reduce Hg contamination.